The Effect of Environmental, Social, and Governance (ESG), COVID-19 on Firm Performance with Firm Life Cycle as a Moderating Variable - Muthiya Dwi Febrianty; Pratana Puspa Midiastuty; Eddy Suranta; Danang Adi Putra (Yayasan Ilomata, 2023)
This research endeavors to present tangible evidence on the impact of environmental, social, and governance (ESG) factors as well as the COVID-19 pandemic on corporate performance, while also considering the moderating influence of the firm life cycle. The conceptual framework applied is the Legitimacy theory, which is utilized to examine the connection between ESG performance, COVID-19, and firm performance. The evaluation of firm performance involves Tobin's Q for assessing firm value and Return on Assets (ROA) for financial performance. Four hypotheses are formulated and subjected to testing. The study utilizes purposive sampling, encompassing all companies listed on the Indonesia Stock Exchange (BEI) between 2017 and 2022, resulting in 235 data observations. The analysis of hypotheses is conducted through the SPSS Statistics 26 application. The findings demonstrate a noteworthy correlation between ESG performance and COVID-19 with financial performance, and the firm life cycle moderates this relationship. However, ESG performance and COVID-19 do not significantly affect market performance or firm value. Additionally, the firm life cycle does not moderate the relationship between ESG and firm value. The implications of the study suggest that ESG factors play a legitimizing role, contributing to an overall improvement in firm performance.